Awareness-Raising Technique in Teaching English to ESP Students - Dwi Settya Mahaputri; Fadilla Taslim (Universitas Negeri Padang, 2014)
College students whose major study not English is called non-English Department students. The non-English department students usually learn English under the branch of ESP (English for Specific Purpose).Teaching and learning English in ESP context is not same with the teaching English as general. ESP is built the process of teaching and learning English of purposes related to students’ needs and useful to perform particular job related to their field of study major. But, in fact, since the students’ realize that their major is not English; they usually don’t interest more in learning English. They think that English is not important to them because there is no correlation with their subject field of study. By that situation, lecturers whose take responsibility in teaching English to non-English department students have to solve that problems. Lecturers can increase student’s interests’ of English by raising their awareness of learning English. Awareness Raising is activities that can be used by lecturers in order to make the students’ notice of English, aware of the useful of English, and make the students’ understand of English subject. The concept of awareness-raising comes from cognitive learning theories which argue as a prerequisite for the restructuring of the learners’ mental representation of the language. In proposing this, lecturers have to guide ESP students in creating their personal cognitive knowledge of patterns and rules in language. To be effective, the technique of awareness-raising must meet and maintain the mutual needs and interest of the students involved.